Using Gramsci: A New Approach, by Michele Filippini. Issue 4 (2nd October 2018) - Chun, Christian W.
Abstract : This review of Michele Filippini's Using Gramsci: A New Approach examines the book not from the perspective of a trained political scientist or economist but rather from that of an applied linguist interested in exploring and developing alternative ethnographic and pedagogic approaches able to utilize the Gramscian frameworks of common-sense and good-sense beliefs, particularly as these approaches pertain to how people view the role of capitalism in their lives. The reviewer thus comes to this book through his own lenses, as do all readers with their own meaning-making perspectives stemming from their lived experiences. In fact, encouraging the embracing of these varied lenses is the central aim of the book, which is intended for a broad range of scholarly disciplines.